2022
DOI: 10.3390/ijerph19095265
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Perceptions of Gender Aspects in a Virtual-Reality-Based Alcohol-Prevention Tool: A Focus Group Study

Abstract: Virtual reality (VR) is an innovative tool for alcohol prevention among adolescents. However, many aspects of virtual simulations for alcohol prevention remained unstudied, and research on opportunities for tailoring such tools to users’ gender using avatar-based pathways is lacking. The present study, therefore, explores adolescents’ perceptions of gender portrayal and gender tailoring using Virtual LimitLab—a VR simulation for building refusal skills for dealing with peer pressure to consume alcohol. Focus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…Another aspect to be considered in future versions of VR simulations is the role of gender in the flirting options because some participants raised the concern that the flirting experience was not optimally portrayed. Prediger et al (21) indicate that aspects of flirting, sexual harassment, and gender issues could well be incorporated into gender-sensitive VR simulations addressing alcohol consumption among adolescents. Due to the relatively homogenous group of respondents with respect to age and prior alcohol and VR experiences, we could not identify any hints on how age or prior experiences might have influenced the perception of Virtual LimitLab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another aspect to be considered in future versions of VR simulations is the role of gender in the flirting options because some participants raised the concern that the flirting experience was not optimally portrayed. Prediger et al (21) indicate that aspects of flirting, sexual harassment, and gender issues could well be incorporated into gender-sensitive VR simulations addressing alcohol consumption among adolescents. Due to the relatively homogenous group of respondents with respect to age and prior alcohol and VR experiences, we could not identify any hints on how age or prior experiences might have influenced the perception of Virtual LimitLab.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, four behavior change functions are represented in the application, which are presented in an overview in Table 1. While a recent cluster-randomized controlled trial could not demonstrate that the Danish VR FestLab simulation had a significant effect on adolescents' alcohol-refusal self-efficacy (20), research on the German Virtual LimitLab version has not yet addressed this issue and has instead focused on perceptions of gender in the simulation (21).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it might lead to the inappropriate homogenisation of within-group differences and exclude adolescents of gender minorities. A previous study conducted by our research group with girls and boys on Virtual LimitLab [17] indicated diverging opinions among the participating adolescents on binary gender-specific tailoring options. Participants raised awareness and questions as to how to better integrate peers with diverse gender identities into the simulation and additionally agreed with conceptualising sexual orientation in a way that is more than hetero-oriented [17].…”
Section: Introductionmentioning
confidence: 75%
“…VR can promote learning in safe environments [15] via immersion and explorative, practicebased first-hand experiences [12] with increased interactivity compared with traditional learning methods [16]. To date, a few interventions have been developed that use VR for alcohol prevention among adolescents [17], including the VR component of the Australian alcohol education program Blurred Minds, the Danish VR FestLab application, and Virtual LimitLab, which is the German version of the VR FestLab. All these interventions target the training of refusal skills and aim to increase users' resistance to peer pressure when offered alcohol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation